The Impact of Organizational Characteristics on the Adoption of Contemporary Cost Management Techniques By the Textile Industry in North Macedonia - Dušica Stevčevska-Srbinoska; Marina Stojanova; Snezhana Hristova; Jadranka Mrsik (Journal of Accounting and Management Information Systems (JAMIS), 2020)
Research Question: What is the association between the choice of contemporary cost management methods and enterprise and employee characteristics? Motivation: Modern techniques of cost accounting assist strategic management of contemporary organization to achieve their strategic objectives. External versus internal, long-term unlike short-term perspective is what differentiates the strategic cost management approach from the traditional cost management system. We draw on previous studies in order to examine the impact of organizational and employee characteristics on the adoption of contemporary cost management methods given the lack of research data in developing countries like North Macedonia. Idea: This research examines the usage of contemporary cost management methods by textile companies headquartered in North Macedonia and encompasses five strategic cost management techniques: activity based costing, product life-cycle, target costing, competitive advantage style and value chain analysis. Also, the study looks into the association of certain organizational characteristics with the implementation of contemporary cost management techniques and compares the findings to the conclusions reached by authors like Rossi (2014), Haldma and Lääts (2002), O'Connor et al. (2011). Data: The field work is based on a questionnaire distributed to companies from the textile industry. Tools: We analyze a sample of 46 surveys (response rate of 81 percent): one survey per garment company. Findings: Even though the initial assumption was that textile enterprises in North Macedonia do not apply contemporary cost management methods in strategic management of operations, the research proved the opposite to be true. However, the use of a chosen method does not depend on demographic characteristics of the respondents or company capital. The search for an implementation motive should be expanded and sought after in the operational and process features of entities. Contribution: This study is expected to increase the awareness about contemporary cost methods and to broaden the understanding of the relationships between organizational and employee factors and management accounting techniques employed.
Keywords: M4; M42; 650; textile companies; contemporary cost management methods; organizational characteristics